New Results of Normed Approach Space - Abbas, Ruaa Kadhim; Hussein, Boushra Youssif (Iraqi Journal of Science, 2022)
In this work, we introduce a new convergence formula. We also define cluster point , δ-Cauchy sequence, δ-convergent, δ-completeness , and define sequentially contraction in approach space. In addition, we prove the contraction condition is necessary and sufficient to get the function is sequentially contraction as well as we put a new structure for the norm in the approach space which is called approach –Banach space, we discuss the normed approach space with uniform condition is a Hausdorff space. Also, we prove a normed approach space is complete if and only if the metric generated from approach space is complete as well as prove every finite –dimensional approach normed space is δ-complete. We prove several results and properties in this field.